Design and development of flipped learning engagement model to enhance student achievement - Shaarani, Ahmad Shaarizan (2021)
Online learning education at higher learning institutions has change over the years as technology evolves. The main purpose of this research is to proposed a new model called Flipped Learning Engagement (FLE) model and conduct a study based on this new proposed model. Based on preliminary analysis, students obtain low grades for programming course at degree level especially for Information and Communication Technology (ICT) as well as for Computer Science fields of study. Since this course is also taken by engineering students, this research involves students from both fields. In order to proposed a new FLE model, this study has conduct a user-friendly test on five constructs namely effectiveness of students’ achievements, learnability, ease of use, flexibility and students’ attitude towards using online learning materials was developed and tested based on Programming Technique course. Usability testing on Programming Technique course was conducted based on quasiexperimental approaches, using interview and observation techniques for Universiti Teknikal Malaysia Melaka (UTeM) students as samples. The experiment test for this study consists of 24 students from Faculty of Information and Communication Technology (FTMK) as well as 48 students from the Faculty of Electrical Engineering (FKE) at UTeM. Various instruments such as questionnaires, explanations on students’ progresses, interview schedule as well as pre and post-test were conducted to collect research data. Usability test was carried out in four separate groups which are Control Technology group (CT) group, Experiment Technology (ET) group, Control Engineering (CE) group and Experiment Engineering group (EE) using t-test. The result of this research founds that the experimental group (ET and EE) who undergo learning and teaching process using proposed FLE model obtain higher result or level of achievements as compare to control group (CT and CE) who followed the conventional approach of teaching and learning. The main contribution of this research is the design and development of FLE model. In addition, this research also contributes to the aspects such as the design and development of Programming Technique MOOC, the design of flipped learning activity and the outcomes of the usability test based on FLE model as well as users experienced which was tested using Programming Technique MOOC based on five constructs. FLE model that have been designed and developed in this research can be used as guidance not only for programming related educations but also for all educators that use flipped learning approach in their learning and teaching process. In the future, researchers can conduct in depth study based on this proposed model and make any improvements by adding new entities that enables the model to be used in any related courses at any level of education.